Properties of high flowable mortar containing high volume palm oil clinker (POC) fine for eco-friendly construction - Kanadasan, Jegathish; Razak, Hashim Abdul; Subramaniam, Vijaya (Elsevier, 2018)
The management of waste material from various industries has been given importance in recent times to create a cleaner environment and sustainable industrial atmosphere. Palm oil clinker (POC), one of the by-products from the incineration process of oil palm shell and fibres in the palm oil mill boilers, has the potential to pollute the environment if not managed appropriately. In this study, the applicability and feasibility of POC fine as a substitute for sand was investigated thoroughly at different replacement levels (0%, 12.5%, 25%, 37.5%, 50%, 62.5%, 75%, 87.5% and 100%). It was found that complete replacement of sand with POC fine has the ability to produce almost 78% of the strength compared to the conventional mix at 56 days. From the perspective of durability, POC fine can produce almost 97% of the long lasting effect with regards to the control mix. The assessment of sustainability shows that POC fine can enhance the engineering environmental index and engineering economic index by 95% and 11%, respectively. Life cycle impact assessment (LCIA) performed proves the ability of POC to promote cleaner and safer environment. This research reveals that POC fine can be regarded as a highly beneficial material contributing substantially towards the sustainability and preservation of sand as a natural resource even when completely substituted.